마오쩌둥 이후 중국 지역 발전 전략의 전환: 불균등 발전에서 권역 협업 기반의 조화로운 발전으로의 진화 - 张丽娜; Lina Zhang; 이승철; Sung-cheol Lee (한국경제지리학회지, 2023)
본 연구의 목적은 마오쩌둥 이후 중국 지역 발전 정책의 진화와 공간 불균등과의 관계를 분석하고자 하는 것이다. 이를 위해 본 논문은 1인당 GRDP 변동계수와 지니계수를 적용하여 중국 31개 시 · 성 · 자치구 간지역 경제력 격차와 지역 발전 정책과의 관계를 분석하였다. 중국의 지역 간 경제력 격차는 1979년 이후 심화되었다가 제10차 5개년 계획(2001~2005년) 이후 중부, 서부, 동북부 지역의 지속적인 정부 주도의 대규모 경제성장 정책에 따라 완화되는 것으로 분석되었다. 그러나 이는 31개 시 · 성 · 자치구 전체를 대상으로 분석한 결과이며, 동부, 중부, 서부, 동북부 4대 지역을 대상으로 GDP 변동계수를 각각 분석했을 때 상이한 결과가 나타났다. 예를 들어, 제10차 5개년 계획 이후 중부 지역 내 격차는 지속적으로 심화되었지만 서부와 동북부의 지역 내 경제력 격차는 지속적으로 완화되었다. 이는 중국의 지역 간 경제력 격차를 완화시키는데 큰 역할을 한것으로 분석되었다. 특히 동부 지역 내 격차는 제12차 5개년 규획(2010~2015년) 이후에도 지속적으로 심화되어 중국 지역 경제력의 수렴 현상이 둔화되는 결과를 가져왔다. 이는 제11차 5개년 규획(2006~2010년) 시기에 본격적으로 시행되었던 중부 권역 발전 정책의 한계에 기인한 것으로 볼 수 있다 The main purpose of this paper is to explore the relationship between the transformation of Chinese regional development policy and trends in spatial inequality in mainland China. More specifically, it has attempted to identify the effects of Chinese regional development policies on regional economic inequality by investigating the coefficient of variation and Gini coefficient with GRDP in the province level. Regional inequality in China had increased from 1979 economic reform, but has eased since the 10th Five Year Plan(2001~2005) due to large-scale state investments in the western, central and northeastern regions. However, the analysis is likely to be resulted from the national level. Trends in regional inequality are differentiated in accordance with the eastern, central, northeastern and western regions. For example, regional inequality in the central region has increased, whereas other three regions has decreased since the 10th Five Year Plan. It has played a role in cutting down regional inequality in the national level. In particular, the central region has kept inequality since the 12th Five Year Guideline. It has led to the convergence of the regional economies in the national level. It has stemmed from some limits to greater regional policies in the Central region enforced in the 11th Five Year Guideline(2005~2010)